Struktur umur dan kelimpahan kumbang badak dan kumbang tanduk (Coleoptera: Scarabaeidae) pada perkebunan kelapa sawit di PTPN VIII Unit Parakan Salak, Kabupaten Sukabumi - Hery Widyanto; Pudjianto Pudjianto; I Wayan Winasa (Perhimpunan Entomologi Indonesia, 2022)
The coconut rhinoceros beetle (Oryctes rhinoceros L.) and brown rhinoceros beetle (Xylotrupes gideon L.) (Coleoptera: Scarabaeidae) are insect pests commonly found in oil palm plantations. Availability of breeding sites is one of factors that can increase the beetle population. Therefore, this study aimed to determine the abundance and age structure of the coconut rhinoceros beetles and brown rhinoceros beetles in the breeding sites located in a plantation with immature and mature stage of oil palms. The results of this study indicated that the abundance of coconut rhinoceros beetle was found to be lower than brown rhinoceros beetle (4.47±13.56 compared to 25.23±16.48 individuals/plot) in the oil palm plantations in PTPN VIII Parakan Salak, Sukabumi Regency. The population of coconut rhinoceros beetle was found in the breeding site located in the plantation with mature oil palms, but not found in the location with immature plants. The age structure of coconut rhinoceros beetle was dominated by the 1st and 2nd instar larvae. The age structures of brown rhinoceros beetles in the breeding sites located in the immature and mature oil palm were similar, and they were dominated by the 1st, 2nd, and 3rd instar larvae. Results of correlation analysis show that there is no correlation between soil chemical characteristics of the breeding site and the beetle population. Soil chemical characteristics at the breeding sites in both locations were relatively similar, and consequently, the abundance and age structure of coconut rhinoceros beetle and brown rhinoceros beetle not significantly different between both locations.